1995
DOI: 10.1074/jbc.270.43.25678
|View full text |Cite
|
Sign up to set email alerts
|

The Membrane Topology of the Rat Sarcoplasmic and Endoplasmic Reticulum Calcium ATPases by in Vitro Translation Scanning

Abstract: The membrane topology of the rat endoplasmic reticulum (ER) and sarcoplasmic reticulum (SR) Ca 2؉ATPases were investigated using in vitro transcription/ translation of fusion vectors containing DNA sequences encoding putative membrane-spanning domains. The sequences of these Ca A construct containing the fifth predicted transmembrane segment was able to act only as a stop transfer sequence. The sixth transmembrane segment did not insert cotranslationally into the membrane. The seventh was able to act as both a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
42
0

Year Published

1998
1998
2012
2012

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 43 publications
5
42
0
Order By: Relevance
“…As a result, the vector assays for both targeting and translocation and the intrinsic signal anchor capacity of a single segment cannot be measured. Insertion of a segment into the M0 vector, which results in a nonglycosylated product, does not necessarily reflect a segment incapable of insertion, as was concluded by various authors (13,16,17,123). FIG.…”
Section: Insertion Of Isolated Hydrophobic Segmentsmentioning
confidence: 71%
See 1 more Smart Citation
“…As a result, the vector assays for both targeting and translocation and the intrinsic signal anchor capacity of a single segment cannot be measured. Insertion of a segment into the M0 vector, which results in a nonglycosylated product, does not necessarily reflect a segment incapable of insertion, as was concluded by various authors (13,16,17,123). FIG.…”
Section: Insertion Of Isolated Hydrophobic Segmentsmentioning
confidence: 71%
“…Although the assembly of some membrane proteins in the ER appears to occur via this mechanism, observations such as the exclusion of hydrophobic segments from the membrane (184,187), the insertion of less hydrophobic sequences (13,16,17,133), and observations made with artificial proteins (65,66) and with C-terminally truncated membrane proteins (37,199) have suggested that the insertion process may be more complicated, depending on the coordinate action of two or more topogenic sequences in the nascent chain. Recently, it has been documented that the ribosome plays a role in the insertion process (49,111,127).…”
Section: Vol 64 2000 Topogenic Signals In Membrane Proteins 23mentioning
confidence: 99%
“…1 Mutational analysis has provided evidence for a role for hydrophilic and carboxylic amino acids in cation occlusion and transport particularly in the fifth and sixth membrane domain and in TM4 and TM7. From proteolysis results M5 and M6 are relatively short and do not insert independently into microsomal membranes in in vitro translation systems and in vivo expression in Xenopus oocytes (7)(8)(9). This membrane pair is relatively easily removed from the membrane after trypsinolysis (1,10).…”
mentioning
confidence: 99%
“…The SERCA2b enzyme contains a 49-amino acid C-terminal extension ("the SERCA2b tail," Fig. 1) that makes up an 11th transmembrane helix (TM11) continuing into an 11-amino acid luminal extension (LE) (3)(4)(5)(6)(7). Analysis of the Ca 2ϩ dependence of Ca 2ϩ transport and ATPase activity at steady state has demonstrated that SERCA2b exhibits markedly higher apparent affinity for cytosolic Ca 2ϩ and lower maximal transport activity than any other SERCA isoform (4, 6, 8 -12).…”
mentioning
confidence: 99%